Photoperiodic responses of the squash bug (Heteroptera: Coreidae): Diapause induction and maintenance - Nechols, James R. (My University, 2013)
The squash bug, Anasa tristis DeGeer, undergoes a reproductive diapause from late summer to spring in northeastern Kansas. In the laboratory, diapause was induced in 100% of adult females reared under photoperiods shorter than 14:10 (L:D) and in a variably lower percentage of the population under all longer photoperiods. The critical photoperiod for diapause induction falls between 14:10 and 14.5:9.5; this range compares closely with prevailing natural daylengths when 50% of the adult population enters diapause in the field. Between October and March, short daylengths maintained, and long daylengths terminated, diapause in field-sampled adults. Under natural daylength at 26°C, the duration of diapause became progressively shorter with advancing sample date. In nature, the photoperiodic maintenance of diapause is completed in most of the population by late May. A prolonged diapause probably serves to prevent premature postdiapause development during the thermally variable spring conditions encountered in Kansas. Some implications of these findings for biological control and pest management programs are discussed.
Citation: Nechols, James R. 1988. “Photoperiodic Responses of the Squash Bug (Heteroptera: Coreidae): Diapause Induction and Maintenance.” Environmental Entomology 17 (3): 427–31. https://doi.org/10.1093/ee/17.3.427.
Keywords: Insecta; Anasa tristis; Photoperiod; Diapause; Squash bug